The Associativity: a local development strategy for Ocamonte (APCO) coffee growers in Santander, Colombia - Ligia Inès Melo Torres; Maria Mercedes Melo Torres; Dora Esther Fonseca Pinto (Acta Agronómica)
The market liberalization policy is forcing business sectors and localities to generate strategies aimed to improving the living conditions of entrepreneurs and at the same time, being competitive. The present study exhibits the major contributions to local development, obtained from the creation associativity strategy of small coffee growers in Ocamonte (APCO), Santander-Colombia. It was observed that contributions evidenced in the dimension improvements as follows: socio-cultural, economic, environmental and policy- institutional, respectively. Given these concerns, a descriptive study with a sample of 45 associates was designed, from which in the second half of 2015, a structured survey was applied, evidencing the perceptions of the associates in relation of their achievements, evidenced associativity for more than 20 years, entering into fair trade agreements, improving their living conditions, being competitive and contributing to local development of their municipality. In fact, these results were corroborated in information obtained in interviews with members of the director board of the coffee growers association, as well as officials of the City Hall and schoolteachers in the association area of influence.